Digital Amanah: Enhancing Member Service Quality in BMT through UGT MOBILE Application - Dea Yasmita Ananda Sari; Khoirini Siva’a Qolbina; Mira Ustanti (ICO EDUSHA, 2025)
This research investigates how service digitalization through the UGT Mobile platform contributes to enhancing the quality of member services in BMT UGT Nusantara, Purwoharjo Branch, within the framework of Islamic microfinance. The study further examines the key barriers encountered during implementation and proposes strategic, sharia-compliant solutions to address them. Using a qualitative case study approach, data were collected via in-depth interviews with the Branch Manager, digital service officers, an Islamic marketing specialist, and active users. Findings reveal that UGT Mobile has substantially improved service quality in four core aspects of digital performance: efficiency reflected in reduced waiting times; reliability evident in system consistency and real-time notifications; system availability through 24-hour accessibility; and privacy ensured via multi-layered data protection.This enhancement aligns with sharia principles (amanah, ihsan, hifz al-mal). Key constraints were low digital literacy among some members (especially the elderly) and limited internet infrastructure. Effective solutions included "outreach" educational approaches, personal assistance, and a hybrid service model. Ultimately, the study concludes that the success of digital transformation in Islamic microfinance institutions relies not only on the technological robustness of applications but equally on educational and value-based engagement strategies that reinforce Islamic ethical frameworks Keywords: Service Digitalization, UGT Mobile, Service Quality, BMT, Digital Literacy, Islamic Finance, Case Study.